A novel strategy for comparative numerical analysis of the response of buried composite and steel pipes subjected to realistic loading scenarios: FEA in cooperation with Taguchi approach. (April 2021) - Azizian, Masoume; Azizian, Mohammad; Rashed, Gholamreza; Mohtadi-Bonab, M.A.; Abazadeh, Babak
Highlights: The Taguchi method is used for process optimization of numerical analysis to supply a targeted study. With a novel strategy, a procedure is developed to capture synergism of the effective factors. The presented procedure able to analyse factors individually and collectively, and it is more efficient from prior methods. Composite pipes are an appropriate option for earthquake-prone areas. The internal pressure is the most serious design constraint for buried composite pipes. Abstract: The main objective of this paper is to perform a comparative Finite Element Analysis (FEA) of the mechanical behaviour of buried GRE composite and X60 steel pipelines under various scenarios with realistic loadings conditions that may be experienced by actual buried pipes. The response of buried pipes is influenced by various factors and their synergistic effects, so in this study, with a novel strategy, a procedure is developed to investigate these synergisms. Firstly, after constructing FE models and validating them with using analytical and previous numerical models available in the literature, these FE models are developed to collaborate with the statistical methods and afterwards, they are taken into account as virtual experiments. FE analysis in cooperation with the Taguchi approach is used to obtain a well-planned set of experiments to get a targeted study. Finally, the obtained results can be used to supply a better understanding of the failure process of buried pipes and optimization of design features of future buried pipelines which may provide a significant insight for installation designs, failure prevention, maintenance strategies for diminishing costs and prevention from catastrophic occurrences. The perspective of the presented strategy shows that it is more efficient and comprehensive than preceding procedures. Both GRE and X60 buried pipes are studied under pseudo-earthquake effects. Results show composite pipes are an appropriate option for earthquake-prone areas.